2017
DOI: 10.1080/14756366.2016.1265523
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis and biological evaluation of novel hydroxy-phenyl-1H-benzimidazoles as radical scavengers and UV-protective agents

Abstract: An ever-increasing incidence of skin neoplastic diseases is registered. Therefore, it is important to protect the skin from the UV radiation that reaches the epidermis and dermis but also to block ROS generated by them. Our attention was attracted in developing new compounds provided with both UV filtering and antioxidant capacities. To this end, 2-phenyl-1H-benzimidazole-5-sulfonic acid (PBSA), a known UV filter, was selected as lead compound for its lack of antioxidant activity, high water solubility and goo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 27 publications
2
25
0
Order By: Relevance
“…Boosters can be small molecules, polymers, or other particles, and mainly act on the rheological properties of the formulation, but also can synergistically interact with the UV filters through antioxidant mechanisms or interfere with the electronic processes of UV radiations absorption. Among these, dihydroxyphenyl benzimidazole carboxylic acid (Oxisol, University of Ferrara European Patent EP2800741) ( Figure 1) have shown a strong antioxidant activity linked to its free radical scavenging activity [16]. Oxisol is devoid of significant UV-filtering activity, but endowed with UV-filtering booster capability if associated with known commercial UVB and UVA filters as reported by Bino and co-workers [16].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Boosters can be small molecules, polymers, or other particles, and mainly act on the rheological properties of the formulation, but also can synergistically interact with the UV filters through antioxidant mechanisms or interfere with the electronic processes of UV radiations absorption. Among these, dihydroxyphenyl benzimidazole carboxylic acid (Oxisol, University of Ferrara European Patent EP2800741) ( Figure 1) have shown a strong antioxidant activity linked to its free radical scavenging activity [16]. Oxisol is devoid of significant UV-filtering activity, but endowed with UV-filtering booster capability if associated with known commercial UVB and UVA filters as reported by Bino and co-workers [16].…”
Section: Introductionmentioning
confidence: 95%
“…Among these, dihydroxyphenyl benzimidazole carboxylic acid (Oxisol, University of Ferrara European Patent EP2800741) ( Figure 1) have shown a strong antioxidant activity linked to its free radical scavenging activity [16]. Oxisol is devoid of significant UV-filtering activity, but endowed with UV-filtering booster capability if associated with known commercial UVB and UVA filters as reported by Bino and co-workers [16]. Titanium dioxide (TiO 2 ) exists in nature in four natural polymorphs [17].…”
Section: Introductionmentioning
confidence: 97%
“…Dihydroxyphenyl benzimidazole carboxylic acid (Oxisol, University of Ferrara European Patent EP2800741) ( Figure 1) is the representative of an interesting new class of UV boosters provided with a powerful radical scavenger profile [9]. Oxisol is devoid of any significant UV-filtering activity, but has an unattended UV-filtering booster capability on well-known UVB and UVA filters (both organic and inorganic) [9]. However, during our studies, the association of Oxisol and physical UV filters (p-UVf) (TiO2 and ZnO) showed some limitations, including a pH range of application that can influence antioxidant activity and color change.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, zinc anti-acne properties have been well known for a century, but zinc is experiencing a second youth during materials or in improving their dispersion; the latter are based on interactions with the energy states of classic filters [8]. Thus, there may be different kinds of boosters [9]: (1) Emollients, which have the ability to disperse the filters in a more effective and stable way; (2) polymers, such as acrylic or polyvinylpyrrolidone copolymers, which improve the thixotropic behavior of the emulsion, giving it better distribution on the skin and maintaining a thin and homogeneous layer on the skin; (3) coating of filtering substances to increase the number of light passages through films with different refractive indexes (multilayer filter effect), bead that increase the particle diameter of the nano-filters contained inside, also reducing their photo-reactivity; (4) hollow spheres that are empty spherical particles with a different refractive index than the polymeric shell and act as a UV scattering center; and finally (5) quencher, that are non-filtering substances that break down the various excited states of the filters, which are essential for stabilizing the filtering system over time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation